2022
DOI: 10.3390/cancers14215332
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Lymphocytes (TILs) in Epithelial Ovarian Cancer: Heterogeneity, Prognostic Impact, and Relationship with Immune Checkpoints

Abstract: Epithelial ovarian cancers (EOC) are often diagnosed at an advanced stage with carcinomatosis and a poor prognosis. First-line treatment is based on a chemotherapy regimen combining a platinum-based drug and a taxane-based drug along with surgery. More than half of the patients will have concern about a recurrence. To improve the outcomes, new therapeutics are needed, and diverse strategies, such as immunotherapy, are currently being tested in EOC. To better understand the global immune contexture in EOC, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 142 publications
0
6
0
Order By: Relevance
“…With histological images, ovarian cancer can be separated into groups with different risk by identifying TILs (35). Different subtypes of TILs in ovarian cancer were also found to differentially affect the progression of ovarian cancer (36,37). From the pathway enrichment results in this study together with spatial transcriptome, we did a novel analysis to determine their relationship.…”
Section: Discussionmentioning
confidence: 94%
“…With histological images, ovarian cancer can be separated into groups with different risk by identifying TILs (35). Different subtypes of TILs in ovarian cancer were also found to differentially affect the progression of ovarian cancer (36,37). From the pathway enrichment results in this study together with spatial transcriptome, we did a novel analysis to determine their relationship.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, in a recent article involving 1078 EOC and 545 CCOC, a significant association was observed for diseasespecific survival in EOC in a univariable analysis [38]. However, the largest series analyzing the relationship between TILs and survival included HGSOC [39]. These studies evaluated different types of infiltrating T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…For ovarian cancer, it has been shown that the presence of TILs positively correlates with survival (70,71). On the other hand, immunosuppressive factors also play a significant role in EOC.…”
Section: Discussionmentioning
confidence: 99%